Educational Entrepreneurship as an Innovative Dimension in the Development of Teachers' Professional Competence - Annisa Cahya Wulandari; Aura Angelina; Frika Fatimah Zahra; Ahmad Zainuri (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
This study aims to examine educational entrepreneurship (edupreneurship) as an innovative dimension in the development of teachers’ professional competence. The study is motivated by the increasing demands of modern education, which require adaptive, creative, and innovative capabilities to respond to dynamic changes. This research employs a library research method by reviewing relevant literature, including academic journals, books, and scholarly articles. The data are analyzed using a qualitative descriptive approach. The findings indicate that educational entrepreneurship is not merely related to economic activities, but rather emphasizes the ability to create value through innovation, creativity, and decision-making within the educational context. Edupreneurship plays a significant role in transforming learning systems to become more adaptive and responsive. From the teacherpreneur perspective, teachers are not only instructors but also innovators and agents of change. Furthermore, educational entrepreneurship contributes to enhancing teachers’ professional competence, particularly in terms of creativity, independence, and instructional innovation. Therefore, educational entrepreneurship can be considered a strategic approach in developing teachers’ professional competence oriented toward educational innovation.